PERLINDUNGAN HUKUM TERHADAP PENDAFTARAN JAMINAN FIDUSIA DENGAN OBJEK BENDA INVENTORY (STOK BARANG DAGANGAN) STUDI PADA PT. BANK DANAMON INDONESIA, TBK CABANG MEDAN - MUHAMMAD AFDHOL (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Hasim Purba3. T. Keizerina Devi A The result of the research shows that regulation in the fiduciary security registration using inventory is the registration to its binding. It is grounded on the stipulations as referred to in Article 12, Article 13, and Article 14 of Law No. 42/1999 on Fiduciary. In addition, the registration of the security binding in fiduciary security will give safer or more secured protection against a creditor if compared to the registration of the object. The protection provided by law against the creditor with the object of fiduciary security using trading stock (inventory) is sufficient, if the security binding is registered in the fiduciary security. With the security binding, the creditor can fulfill his rights by executing the object of fiduciary security in line with what is stated in the object detail of the fiduciary security certificate and if the object used as the fiduciary object is not in line with the detail attachment, the creditor can still claim for his rights in accordance with the value of the object of fiduciary as mentioned in the statement of Fiduciary Security Registration.Keywords: Legal Protection, Fiduciary Security, Trading Stock (Inventory).